2023
DOI: 10.3390/antibiotics12071118
|View full text |Cite
|
Sign up to set email alerts
|

Global Antimicrobial Resistance Gene Study of Helicobacter pylori: Comparison of Detection Tools, ARG and Efflux Pump Gene Analysis, Worldwide Epidemiological Distribution, and Information Related to the Antimicrobial-Resistant Phenotype

Abstract: We conducted a global-scale study to identify H. pylori antimicrobial-resistant genes (ARG), address their global distribution, and understand their effect on the antimicrobial resistance (AMR) phenotypes of the clinical isolates. We identified ARG using several well-known tools against extensive bacterial ARG databases, then analyzed their correlation with clinical antibiogram data from dozens of patients across countries. This revealed that combining multiple tools and databases, followed by manual selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 86 publications
0
1
0
Order By: Relevance
“…Conversely, multiple studies reported that administering probiotics before and after eradication therapy for H. pylori rapidly reinstates intestinal microbiota (Figure 5), especially Bacillus and Lactic acid bacteria [117,131,132]. Another issue is antimicrobial resistance regarding H. pylori management that leads to pharmacological intervention failure throughout the globe [66,80,[133][134][135][136].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, multiple studies reported that administering probiotics before and after eradication therapy for H. pylori rapidly reinstates intestinal microbiota (Figure 5), especially Bacillus and Lactic acid bacteria [117,131,132]. Another issue is antimicrobial resistance regarding H. pylori management that leads to pharmacological intervention failure throughout the globe [66,80,[133][134][135][136].…”
Section: Discussionmentioning
confidence: 99%